How often do our liver core biopsies reach current definitions of adequacy?. Issue 12 (17th July 2013) - Fryer, Eve; Wang, Lai Mun; Verrill, Clare; Fleming, Kenneth
Abstract : Needle core biopsy is a key tool in diagnosis and assessment of many medical liver diseases, but there is evidence that the combination of small size of the specimen obtained and the patchy nature of many of these diseases can result in misdiagnosis or incorrect staging. The Royal College of Pathologists has therefore published guidelines for assessment of adequacy. To assess whether these guidelines were being observed, we reviewed cases reported in our department over a 15-year period. Results showed that only 19.8% of cores would be considered adequate, 56.4% were suboptimal and 23.8% were inadequate. We discuss the issues around recommendations on the minimum size of liver biopsies, potential factors limiting biopsy size and whether further refinement of the guidelines for adequacy is required.